O estatuto transcendente das perfectiones simpliciter na metafísica de João Duns Scotus - Leite, Thiago Soares (2013)
This PhD thesis aims to defend the transcendent status of pure perfections. In order to confirm our hypothesis, this study adopts the following route: in the introduction, we present the main elements of metaphysics before Duns Scotus that most influenced the Doctor Subtilis s system. There are three steps: the conception of science and metaphysics of substance put forward by Aristotle; the discussion about the object of study of first philosophy between the medieval Arabs, in particular, in the philosophies of Avicenna and Averroes; the concepts of being and essential order on Henry of Ghent. Holding these elements in mind, the first chapter contextualizes the scotistic conception of metaphysics. It deals with the following themes: the concept and the object of metaphysics according to Duns Scotus; the concept of being as the first object of human intellect; the univocity of being; the so called "second beginning of metaphysics". Since being is the first class of transcendent notions, scotistic metaphysics is configured not only as ontology, but also as a transcendent science. In this sense, it is necessary to clarify the concept of transcendent proposed by Duns Scotus, as well as dealing with transcendent classes too, namely: the coextensive attributes, the disjunctive attributes and the pure perfections. To carry out this task is the goal of our second chapter. As far as is known, the De primo principio is the first philosophical treatise entirely dedicated to prove the existence of God written by a Medieval Latin philosopher. Therefore, we center our discussion in this work which is the aim of the third chapter of the present study. Finally, our fourth and last chapter presents two ways in favor of the transcendent status of pure perfections.